Falcine venous plexus within the falx cerebri: Anatomical and scanning electron microscopic findings and clinical significance - Tatarlı, Necati; Ceylan, Davut; Canaz, Hüseyin; Tokmak, Mehmet; Bay Hacıoğlu, Hüsniye; Şeker, Aşkın; Keleş, Evren; Kılıç, Türker; Çavdar, Safiye (My University, 2013)
Background: Only limited attention has been paid to the anatomy and clinical importance of the falcine venous plexus. The aim of this study was to evaluate the falcine venous plexus anatomically using scanning electron microscopy (SEM), and to provide guidance for neurosurgical approaches. Methods: Latex or ink was injected into the superior and inferior sagittal sinus. The falcine venous plexus lying within the connective tissue of the falx cerebri was observed by dividing the falx into thirds (anterior, middle and posterior). Further, the SEM appearance of the falcine venous plexus was evaluated. Results: The anterior third of the falx cerebri consisted of small diameter falcine venous vessels. These vessels were localized close to either the superior or inferior sagittal sinus, and none extended as far as mid-falx cerebri levels in any of the 16 cases. They communicated with either superior or inferior sagittal sinuses, but not with both of these sinuses. In the middle third of the falx cerebri, the majority of the vessels of the falcine venous plexus had larger diameter compared to those of the anterior third. These vessels extended the length of the falx cerebri levels. They communicated with both superior and inferior sagittal sinuses. In the posterior third of the falx cerebri, the vessels of the falcine venous plexuses had the largest diameter and were located at the junction of the inferior sagittal sinus and the straight sinus. They were localized at the lower two-thirds of the falx cerebri. In all cases, the dense venous networks communicated with the inferior sagittal sinus but not with the superior sagittal sinus. The falcine venous plexus observed in the posterior third of the falx cerebri was denser than in the anterior and middle portions. The SEM revealed small vessels whose diameter ranged between 42 and 138 µm. The vessels of the falcine venous plexus in the anterior third had a mean diameter of 0.42 ± 0.1 mm, in the middle third a mean diameter of 0.87 ± 0.17 mm, and in the posterior third, 1.38 ± 0.21 mm. Conclusion: The falcine venous plexus is a network of venous channels that exists within the connective tissue of the falx; the sizes and patterns of communication of these structures showed regional differences. Neurosurgeons should be aware of the regional differences when making an incision or puncturing the falx during a surgical approach.
Keywords: Falcine Venous Plexus; Falx Cerebri Venous Anatomy; Falx Meningioma; Inferior Sagittal Sinus; Neuroanatomy; Superior Sagittal Sinus